Effects of dietary supplementation of natural astaxanthin from Haematococcus pluvialis on antioxidant capacity, lipid metabolism, and accumulation in the egg yolk of laying hens - Gao, Shan (Poult Sci, 2020)
The present study evaluated the effects of natural astaxanthin (ASTA) from Haematococcus pluvialis on the antioxidant capacity, lipid metabolism, and ASTA accumulation in the egg yolk of laying hens. Hy-Line Brown layers (n = 288, 50 wk old) were randomly assigned to 1 of 4 dietary treatment groups. Each group had 6 replicates of 12 hens each. All birds were given a corn-soybean meal–based diet containing 0, 25, 50, or 100 mg/kg ASTA for 6 wk. The results showed that the total antioxidant capacity, superoxide dismutase level, and glutathione peroxidase level in the plasma, livers, and egg yolks were significantly increased in the ASTA groups compared with those of the control group (P < 0.05), whereas the content of malondialdehyde linearly decreased (P < 0.05). The plasma levels of high-density and very-low-density lipoprotein cholesterol in the ASTA groups were significantly higher than those in the control group (P < 0.05). In addition, ASTA supplementation decreased low-density lipoprotein cholesterol and triglyceride plasma levels (P < 0.05). However, there were no significant differences in the other lipid metabolism parameters among the ASTA-supplemented groups relative to the control group except for an increase in high-density lipoprotein cholesterol in the liver. Compared with the control, dietary ASTA supplementation significantly increased the enrichment of ASTA in egg yolks at the end of week 2, 4, and 6 (P < 0.05). The mRNA expression of scavenger receptor class B type 1 (SCARB1) and very-low-density lipoprotein receptor (VLDLR) in the ASTA groups was markedly higher (P < 0.05) than that in the control group in the liver and ovaries, respectively. In conclusion, these results suggest that dietary ASTA enhances the antioxidant capacity and regulates lipid metabolism in laying hens. ASTA enrichment in egg yolks may be closely related to the upregulation of SCARB1 and VLDLR gene expression.